Regional trends in avoidable hospitalisations due to complications among population with diabetes in Finland in 1996−2011: a register-based cohort study - Manderbacka, Kristiina (BMJ Open, 2016)
OBJECTIVES: Diabetes requires continuous medical care including prevention of acute complications and risk reduction for long-term complications. Diabetic complications impose a substantial burden on public health and care delivery. We examined trends in regional differences in hospitalisations due to diabetes-related complications among the total diabetes population in Finland. RESEARCH DESIGN: A longitudinal register-based cohort study 1996−2011 among a total population with diabetes in Finland. PARTICIPANTS: All persons with diabetes identified from several administrative registers in Finland in 1964−2011 and alive on 1 January 1996. OUTCOME MEASURES: We examined hospitalisations due to diabetes-related short-term and long-term complications, uncomplicated diabetes, myocardial infarction, stroke, lower extremity amputation and end-stage renal disease (ESRD). We calculated annual age-adjusted rates per 10 000 person years and the systematic component of variation. Multilevel models were used for studying time trends in regional variation. RESULTS: There was a steep decline in complication-related hospitalisation rates during the study period. The decline was relatively small in ESRD (30%), whereas rates of hospitalisations for short-term and long-term complications as well as uncomplicated diabetes diminished by about 80%. The overall correlation between hospital district intercepts and slopes in time was −0.72 (p<0.001) among men and −0.99 (p<0.001) among women indicating diminishing variation. Diminishing variation was found in each of the complications studied. The variation was mainly distributed at the health centre level. CONCLUSIONS: Our study suggests that the prevention of complications among persons with diabetes has improved in Finland between 1996 and 2011. The results further suggest that the prevention of complications has become more uniform throughout the country.